2009
DOI: 10.1093/chemse/bjp079
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Odorants on Respiratory Patterns in Sleep

Abstract: To assess the feasibility of using odors as a potential mechanism for treating sleep apnea, we set out to test the hypothesis that odorants delivered during sleep would modify respiratory patterns without inducing arousal or wake in healthy sleepers. We used 2 mildly trigeminal odorants: the pleasant lavender and unpleasant vetiver oil and 2 pure olfactory odorants: the pleasant vanillin and unpleasant ammonium sulfide. During sleep, an olfactometer delivered a transient odorant every 9, 12, or 15 min (randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 45 publications
2
56
0
7
Order By: Relevance
“…The reference lists of these identified studies and systematic reviews, along with OVID Medline electronic article mappings, yielded eight additional studies meeting the inclusion criteria. A total of 15 human studies on inhaled essential oils and their effect on sleep were found, 5,[36][37][38][39][40][41][42][43][44][45][46][47][48][49] and their methods and results were summarized and compared (Table 1).…”
Section: Study Descriptionmentioning
confidence: 99%
“…The reference lists of these identified studies and systematic reviews, along with OVID Medline electronic article mappings, yielded eight additional studies meeting the inclusion criteria. A total of 15 human studies on inhaled essential oils and their effect on sleep were found, 5,[36][37][38][39][40][41][42][43][44][45][46][47][48][49] and their methods and results were summarized and compared (Table 1).…”
Section: Study Descriptionmentioning
confidence: 99%
“…Olfactory stimulation during sleep significantly alters breathing patterns (Arzi et al 2010). Arzi et al (2012) paired different tones with different odors to demonstrate that simple condition paradigms using the olfactory sniff response (longer in-breaths while presenting positive odors compared to the inbreaths while presenting negative odors) can be carried out during sleep and that the effects carry over to waking life.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, evidence of true sleep learning-acquiring new declarative knowledge while sleeping-remains elusive. npg n e w s a n d v i e w s sniff response 13 . When subjects inhale a pleasant odor, the inhalation volume is greater than when they inhale an unpleasant odor 14 , and, although an earlier study by the same group failed to find a difference between pleasant and unpleasant odors during sleep 13 , Arzi et al 2 found significantly larger inhalation volumes after pleasant odors than after unpleasant ones, during both REM and non-REM sleep.…”
mentioning
confidence: 99%